Correlated disorder as a tunable switch between trapping and conduction in quantum ion channels - Da Silva Ramos, Iara Patrícia; Gandolfi Lanzini, Rafael; Brunnet, Leonardo; Prado, Sandra D. (Frontiers in Quantum Science and Technology, 2025)
Quantum transport efficiency is influenced by mechanisms beyond coherence, including correlated disorder, which can balance localization and mobility to produce anomalous phenomena such as quantum rogue waves. Motivated by recent findings, we investigate the impact of correlated on-site energies in a linear quantum chain modeling a biological ion channel. The system is described by a tight-binding Hamiltonian with Lindblad operators representing source and drain. The average traversal time across the channel increases logarithmically with the correlation parameter, mirroring the growth of rogue-wave probability and indicating the emergence of temporary trapped states that slow transport. These results demonstrate that correlated disorder significantly influences ion transport even in small disordered systems.